Effect of offline bullying on online unethical behavior among college students: the mediating roles of relative deprivation and anger rumination - Lin, Ying; Tang, Zhiwen; Xing, Qiang (Frontiers in Psychology, 2024)
This research delves into the correlation between offline bullying and online unethical behavior among college students; and examines the potential mediating influences of anger rumination and perceived relative deprivation. The findings suggest that anger rumination, perceived relative deprivation, offline bullying, and online unethical behavior exhibit significant positive correlations with each other. Offline bullying is a strong predictor of online unethical behavior among college students, with the dual mediating effects of perceived relative deprivation and anger rumination on the relationship between offline bullying and online unethical behavior. This suggests that offline bullying directly influences college students' online unethical behavior and also influences it indirectly through anger rumination and perceived relative deprivation.